Lessons of the financial crisis for the design of national pension systems - Burtless, Gary (Munich, 2009)
"The recent financial crisis and historical record suggest important lessons about the design of national pension systems. First, wide fluctuation in asset returns makes it hard for well-informed savers to select a saving rate or a sensible investment strategy for DC pensions. Workers who follow identical investment strategies but who retire a few years apart can receive DC pensions that are startlingly unequal. Second, it is hard for ordinary workers, as opposed to optimal planners, to make sensible choices about portfolio allocation. Their investment errors mean that actual returns fall short of the theoretical returns that could be earned by a well-informed, disciplined investor."